2014
DOI: 10.1371/journal.pone.0100832
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Mouse Sperm Impairs Embryo Development, Fetal Growth and Alters Adiposity and Glucose Regulation in Female Offspring

Abstract: Paternal health cues are able to program the health of the next generation however the mechanism for this transmission is unknown. Reactive oxygen species (ROS) are increased in many paternal pathologies, some of which program offspring health, and are known to induce DNA damage and alter the methylation pattern of chromatin. We therefore investigated whether a chemically induced increase of ROS in sperm impairs embryo, pregnancy and offspring health. Mouse sperm was exposed to 1500 µM of hydrogen peroxide (H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 60 publications
5
85
0
3
Order By: Relevance
“…In a study conducted in mice it was shown that F 0 sperm with high concentrations of ROS programs female F 1 for metabolic syndrome and obesity; interestingly male offspring was less affected, demonstrating sex-specific impacts as was shown in the present study [50].…”
Section: Discussionsupporting
confidence: 81%
“…In a study conducted in mice it was shown that F 0 sperm with high concentrations of ROS programs female F 1 for metabolic syndrome and obesity; interestingly male offspring was less affected, demonstrating sex-specific impacts as was shown in the present study [50].…”
Section: Discussionsupporting
confidence: 81%
“…Unfortunately, 8OHdG can be abundant within spermatozoa, particularly within sub-fertile populations, elevating the likelihood that damaged DNA will be contributed to the zygote at fertilization . Further to this, the zygote has been demonstrated to possess a restricted capacity for 8OHdG repair, allowing progression through S-phase in the presence of unrepaired oxidative DNA damage (Ronen and Glickman, 2001;Vinson and Hales, 2002;Aitken et al, 2009;Chabory et al, 2009;Takahashi, 2012;Lane et al, 2014). The current manuscript has characterized BER in the mouse pre-S-phase zygote, revealing a low abundance of the first enzyme in the BER pathway, OGG1, thereby explaining the limited capacity for 8OHdG repair at this early developmental stage.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, transversion mutations within the zygote have the propensity to irreversibly alter gene expression profiles and thence the fidelity of normal embryonic development (Bruner et al, 2000;Wu et al, 2013;Ohno et al, 2014). Despite the importance of repairing oxidative DNA damage at this early stage of development, gametes harboring high levels of 8OHdG at the time of fertilization are known to undergo inadequate DNA repair in the zygote, resulting in detrimental effects on the pre-implantation development of the embryo (Takahashi, 2012;Lane et al, 2014) and on fetal growth and development (Chabory et al, 2009;Lane et al, 2014), as well as defects in offspring, including cancer and a significant reduction in lifespan (Ronen and Glickman, 2001;Vinson and Hales, 2002;Aitken et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Increased serum cholesterol without marked increases to body weight in a rabbit model has previously been reported to cause sperm dysfunction with reduced sperm motility, count, morphology, capacitation, and semen volume (64). Additionally, exposure to increasing in vitro concentrations of both cholesterols and FFA in human sperm caused increased levels of oxidative stress (30), with chemically induced increases in sperm oxidative stress previously reported to program obesity and metabolic syndrome in female offspring (32).…”
Section: Short-term Founder Diet/exercise Intervention Restored Adipomentioning
confidence: 94%